Behavioral Counseling with Self Management Techniques to Improve the Discipline of Students Addicted to Online Games - Heri Fadli Wahyudi; Siti Maulida (Penerbit Hellow Pustaka, 2025)
Online game addiction is carried out by students who lack time discipline and play too much online games so they often stay up late and procrastinate doing their coursework. Therefore, to help clients overcome their problems, behavioral counseling is carried out using self-management techniques. This research aims to determine the application of self-management techniques to improve the discipline of students addicted to online games and the impact of self-management techniques to improve the discipline of students addicted to online games. This research uses a qualitative approach with a case study type which is one of the research strategies for carefully investigating a matter or phenomenon by collecting complete information using data collection procedures, while the data collection procedures in this research use interviews, observation and documentation. The research results show that the counseling process using self-management techniques begins with problem identification which is carried out twice, once before counseling and once again on the first day of counseling, and continues with diagnosis, prognosis and treatment carried out at the first meeting. Then continued with the evaluation carried out at the last meeting, namely the fourth meeting. The counseling process carried out has proven to be able to improve the discipline of students who are addicted to online games. This can be proven by changes in their behavior, they are able to manage their time with the help of the daily activity schedule made by the counselee during the counseling process.